Is there a relation between dental anxiety, fear and general psychological status? - Yildirim, Tuba Talo; Dundar, Serkan; Bozoglan, Alihan; Karaman, Tahir; Dildes, Neval; Kaya, Filiz Acun; Alan, Hilas (Peerj Inc, 2017)
Background. Dental anxiety is a widespread problem in many populations. This problem can be a barrier to dental care and may lead to poor oral health. Dental anxiety may be related to psychological status. Aims. The aim of the present study was to assess the levels of dental anxiety, dental fear, Beck Depression, and state-trait anxiety according to age, gender and education level in patients at the periodontology clinic in the Diyarbak?r Mouth and Dental Health Center. Study Design. A total of 231 patients (115 males, 116 females) filled out dental fear scale (DFS), dental anxiety scale (DAS), Beck Depression Inventory (BDI), state-trait anxiety inventory-state (STAI-S), and state-trait anxiety inventory-trait (STAI-T) questionnaires, and evaluations of DFS, DAS, BDI, STAI-S, and STAI-T were conducted according to age, gender, and education level. Results. The mean DFS, DAS, BDI, STAI-T, and STAI -S were 45.64, 9.15, 13.16, 38.90, and 40.18, respectively. There was a significant association among DFS, DAS, BDI, STAI-S, and STAI-T (p < 0.05). These surveys scores were significantly higher in females than males (p < 0.05). The results of this study indicated that gender age and education level have important effects on DFS, DAS, BDI, STAI-S, and STAI-T (p < 0.05). Conclusion. Dental anxiety and dental fear were found to be related to psychological status (BDI, STAI-S, and STAI-T) over time. There are some patients with unaddressed psychological distress.
Keywords: Depression; Anxiety; Dental anxiety; Dental fear